Stepless shape morphing polymer. Issue 1 (4th July 2022) - Min, Lei; Zhu, Min; Lu, Hanlun; Li, Yao; Fan, Longfei; Zhang, Mingqiu; Rong, Minzhi
Abstract: To change the situation of shape memory polymers (SMPs) that can only remember very few shapes and enable discretional morphing for practical application, the authors report a reversible stepless multiple SMP derived from ultrahigh molecular weight polyethylene (UHMWPE). As the crystals of semi‐crystalline polymers are assembled by those with slightly different melting temperatures, and each type of crystal can remember a single shape, the crystalline region of UHMWPE is allowed to remember plenty of temporary shapes after programming. Changing the temperature of the programmed polymer within the melting/crystallization temperature ranges would lead to releasing/recovery of the memorized temporary shapes. Accordingly, multiple shape memory effects can be easily realized without an elaborate design of material structure and training process in advance as before. The temperature‐dependent adjustability of the analog capacitor and soft lens with embedded programmed UHMWPE as actuators, characterized by the continuous/random/proportional responsivity, further reveals the utilization prospects of the controllable reversible stepless discretionary morphing effect. Moreover, the maximum work density of the programmed UHMWPE is found to be 210 kJ/m 3, which is more than 10 times of piezoelectric ceramics, so that it can serve as a proof‐of‐concept mechanical driver for reversibly pumping of ethanediol‐droplet upon heating/cooling. Abstract : Reversible stepless discretionary morphing polymer is produced by simply training commercial ultrahigh molecular weight polyethylene (UHMWPE) via thermal treatment associated stretching. The key issue is that the crystals of UHMWPE memorize lots of temporary shapes as independent switching phases. A discretionary number of shape memory effects can be easily realized by changing the temperature of the programmed polymer within the melting/crystallization temperature ranges.